Rationale, Design, and Progress of the ENhanced Control of Hypertension ANd Thrombolysis Stroke Study (ENCHANTED) Trial: An International Multicenter 2 × 2 Quasi-Factorial Randomized Controlled Trial of Low- vs. Standard-Dose rt-PA and Early Intensive vs. Guideline-Recommended Blood Pressure Lowering in Patients with Acute Ischaemic Stroke Eligible for Thrombolysis Treatment. Issue 5 (July 2015) - Huang, Yining; Sharma, Vijay K.; Robinson, Thompson; Lindley, Richard I.; Chen, Xiaoying; Kim, Jong Sung; Lavados, Pablo; Olavarría, Verónica; Arima, Hisatomi; Fuentes, Sully; Nguyen, Huy Thang; Lee, Tsong-Hai; et al.
Rationale: Controversy exists over the optimal dose of intravenous (iv) recombinant tissue plasminogen activator (rt-PA) and degree of blood pressure (BP) control in acute ischaemic stroke (AIS). Asian studies suggest low-dose (0·6 mg/kg) is more efficacious than standard-dose (0·9 mg/kg) iv rt-PA, and guidelines recommend reducing systolic BP to <185 mmHg before and <180 mmHg after use of iv rt-PA, despite observational studies indicating better outcomes at much lower (<140 mmHg) systolic BP levels in this patient group. Aims: The study aims to assess in thrombolysis-eligible AIS patients whether: (i) low-dose (0·6 mg/kg body weight; maximum 60 mg) iv rt-PA has non-inferior efficacy and lower risk of symptomatic intracerebral haemorrhage (sICH) compared to standard-dose (0·9 mg/kg body weight; maximum 90 mg) iv rt-PA; and (ii) early intensive BP lowering (systolic target 130–140 mmHg) has superior efficacy and lower risk of any ICH compared to guideline-recommended BP control (systolic target < 180 mmHg). Design: The ENhanced Control of Hypertension And Thrombolysis strokE stuDy (ENCHANTED) trial is an independent, 2 × 2 quasi-factorial, active-comparison, prospective, randomized, open blinded endpoint (PROBE), clinical trial that is evaluating Arm [A] 'rt-PA dose' and/or Arm [B] 'BP control', using central Internet randomization and data collection in patients fulfilling local criteria for thrombolysis and clinician uncertainty over the study treatments. The treatment arms will be analyzed separately. Study outcomes: The primary study outcome in both trial Arms is death or disability according to the modified Rankin scale (mRS, scores 2–6) assessed at 90 days. Secondary outcomes include sICH, any ICH, a shift ('improvement') in function across mRS scores, separately on death and disability, early neurological deterioration, recurrent major vascular events, health-related quality of life, length of hospital stay, need for permanent residential care, and health care costs. Results: Following launch of the trial in February 2012, the study has recruited more than 2500 patients across a global network of approximately 100 sites in 15 countries. The required sample sizes are 3300 for Arm [A] and 2300 for Arm [B], which will provide >90% power to detect non-inferiority of low-dose iv rt-PA and superiority of intensive BP lowering on the primary clinical outcome, respectively. Conclusions: Low-dose iv rt-PA and early intensive BP lowering could provide more affordable and safer use of thrombolysis treatment for patients with AIS worldwide.